Planetary Boundary Layer Height Modulates Aerosol—Water Vapor Interactions During Winter in the Megacity of Delhi. Issue 24 (15th December 2021) - S. Raj, Subha; Krüger, Ovid O.; Sharma, Amit; Panda, Upasana; Pöhlker, Christopher; Walter, David; Förster, Jan‐David; Singh, Rishi Pal; S., Swetha; Klimach, Thomas; Darbyshire, Eoghan; Martin, Scot T.; et al.
Abstract: The Indo‐Gangetic Plain (IGP) is one of the dominant sources of air pollution worldwide. During winter, the variations in planetary boundary layer (PBL) height, driven by a strong radiative thermal inversion, affect the regional air pollution dispersion. To date, measurements of aerosol‐water vapor interactions, especially cloud condensation nuclei (CCN) activity, are limited in the Indian subcontinent, causing large uncertainties in radiative forcing estimates of aerosol‐cloud interactions. We present the results of a one‐month field campaign (February‐March 2018) in the megacity, Delhi, a significant polluter in the IGP. We measured the composition of fine particulate matter (PM1 ) and size‐resolved CCN properties over a wide range of water vapor supersaturations. The analysis includes PBL modeling, backward trajectories, receptor models and fire spots to elucidate the influence of PBL and air mass origins on aerosols. The aerosol properties depended strongly on PBL height and a simple power‐law fit could parameterize the observed correlations of PM1 mass, aerosol particle number and CCN number with PBL height, indicating PBL induced changes in aerosol accumulation. The low inorganic mass fractions, low aerosol hygroscopicity and high externally mixed weakly CCN‐active particles under low PBL height ( < $< $ 100 m) indicated the influence of PBL on aerosol aging processes. In contrast, aerosol properties did not depend strongly on air mass origins or wind direction, implying that the observed aerosol and CCN are from local emissions. An error function could parameterize the relationship between CCN number and supersaturation throughout the campaign. Key Points: Planetary boundary layer height ( H BL ) is the major driving force of aerosol accumulation and aging processes in Delhi during late winter Lower aerosol hygroscopicity and greater external mixing under low H BL Increased CCN number concentration under low H BL due to higher aerosol concentration